Investigation of novel penetration enhancer lawsonia inermis for drug delivery through nail plate - Singh, Vikram; Gupta, R. D.; Teotia, U. V. S. (Journal of Applied Pharmaceutical Research, 2014)
Nail fungus infections may be very painful and can seriously harm through systemic circulation if untreated. In this study we try to find out and formulate the natural penetration enhancer(PEs). Lawsonia Inermis leafs were used as a penetration enhancer. To extract the penetration enhancer extraction was done with methanol and dried, which shows hundred percent penetrations across the nail plate. Human cadaver nail plate (dry weight 45.8 mg, thickness 220 Âµm) defatted with chloroform: methanol (2:1) was used for penetration study. Diffusion study with the help of franz diffusion cell with phosphate buffer saline. The transungual film F32 evaluated for the physical properties â %Drug Content 97.1Â±0.03, Weight variation 180Â±2.10, Thickness 0.21Â±0.01, Flatness 99%, Folding endurance 180Â±3, WVTR 3.143Â±0.436, %Moisture content3.823Â±0.23. The drug moved across the nail plate in near to first order manner and support by the pepass ânâ value i.e. 0.87. The formulation with the Lawsonia Inermisâs extract penetrates the 2.09% more drug through nail plate. The present study can claim that the Lawsonia Inermis as a potent penetration enhancer for transungual delivery for which the penetration is a limiting factor.